Tantangan Penambangan Gas dan Minyak di Laut Natuna Indonesia - Early Vannya Rianty; Erni Mulyanie (Kilau Publishing, 2024)
This study aims to identify and analyze the challenges faced in oil and gas mining activities in the Natuna Sea, Indonesia.The Natuna region has the largest natural gas reserves in the Asia Pacific and is an important strategic area for national energy security. However, oil and gas management in the region faces a variety of complex challenges. This research uses a literature study approach. The results show that the development of the oil and gas sector in Natuna requires international cooperation, the implementation of incentive policies for investors, as well as strengthening diplomacy and maritime defense to maintain regional stability. In addition, there is a need to implement environmentally friendly technology and strict sustainability standards to mitigate the impact of exploration on marine ecosystems.